Human papillomavirus and head and neck squamous cell carcinomas in the South-East of France: prevalence, viral expression, and prognostic implications. (May 2013) - Gavid, Marie; Pillet, Sylvie; Pozzetto, Bruno; Oriol, Mathieu; Dumollard, Jean-Marc; Timoshenko, Andrei P.; Martin, Christian; Prades, Jean-Michel
Abstract Conclusion: Human papillomavirus (HPV) infection, especially by HPV 16, is frequently detected in oropharyngeal squamous cell carcinoma (OSCC). The expression of viral oncoproteins in tumoral tissues of OSCCs suggests the implication of HPV in tumorogenesis. It should now be systematically detected and considered in each patient's treatment and outcome. Objectives: To investigate the prevalence of HPV infection, the oncogenic role of HPV in patients from the South-East of France with head and neck squamous cell carcinoma (HNSCC), and the resulting clinical implications. Methods: Biopsy samples from 200 patients with HNSCC were analyzed. For each patient, one or two biopsies of tumoral tissue were analyzed simultaneously with a biopsy of healthy tissue. Fresh frozen tissues were tested by molecular techniques for HPV DNA detection and genotyping as well as mRNA expression of oncoproteins E6 and E7. Expression of p16 was also analyzed by immunohistochemical staining. Results: HPV DNA tested positive in 11.5% of biopsy samples. The HPV prevalence was higher in OSCCs (91.3 vs 27.3, p < 0.0001) and in patients not consuming tobacco (65.2% vs 95.4%, p < 0.0001). The estimated 3-year overall survival rates were 67.0% for HPV-infected patients versus 39.9% for non-infected patients. The high-risk HPV 16 was the most common type detected (65.2%). In 12 of 18 patients exhibiting DNA of high-risk HPV in their tumor tissue, the same viral genome was also present in normal tissue. E6 and E7 expression was found in 9 of 14 tumoral biopsies tested for these markers.